Uranium remediation using modified Vigna radiata waste biomass. (May 2017) - Naeem, Hafiza; Bhatti, Haq Nawaz; Sadaf, Sana; Iqbal, Munawar
Abstract: Present study was designed to explore the possibility of Vigna radiata biomass for recovery of uranium ions. Various fundamental process parameters i.e., pH, contact time, temperature and initial uranium ions concentration were optimized and maximum uranium removal (230 mg/g) was achieved at pH 4, biosorbent dose 0.05 g, contact time 60 min contact time and temperature 40 °C using 400 mg/L uranium ions concentration. The biomass was also pre-treated by different physical and chemical pretreatments to check out their effect on the adsorption capacity. Different kinetic and equilibrium models were applied to the experimental data to understand the uranium adsorption mechanism. Freundlich isotherm and pseudo-second order kinetic model explained well the adsorption of uranium ions onto Vigna radiata biomass. The biomass physical and chemical pretreatments significantly affected the uranium adsorption and CH3 COOH 0.15 M solution found out to be efficient for de-sorption. FT-IR analysis of native and loaded biomass confirmed the involvement of carbonyl and hydroxyl groups in the uranium adsorption process. The results outcome revealed that Vigna radiata biomass can be used for uranium adsorption in view of low cost and high adsorption efficiency. Graphical abstract: Highlights: Uranium (U) adsorption was carried out using modified low cast V. radiata biomass. At optimized conditions, up to 230 mg/g U adsorption was achieved. CH3 COOH solution found out to be efficient for U recovery. FT-IR study confirmed the involvement of carbonyl and hydroxyl in U adsorption. Modified V. radiata biomass could be used as for the adsorption of radioactive metal adsorption.